Maternal supplementation with fishmeal protects against late gestation endotoxin-induced fetal programming of the ovine hypothalamic-pituitary-adrenal axis. (1st May 2014) - Fisher, R. E.; Or'Rashid, M.; Quinton, M.; AlZahal, O.; Boermans, H. J.; McBride, B. W.; Karrow, N. A.
Abstract : Adverse uterine environments caused by maternal stress (such as bacterial endotoxin) can alter programming of the fetal hypothalamic–pituitary–adrenal axis (HPAA) rendering offspring susceptible to various adulthood diseases. Thus, protection against this type of stress may be critical for ensuring offspring health. The present study was designed to determine if maternal supplementation with omega-3 polyunsaturated fatty acids (n-3 PUFAs) during pregnancy helps to protect against stress-induced fetal programming. Briefly, 53 ewes were fed a diet supplemented with fishmeal (FM) or soybean meal (SM) from day 100 of gestation (gd100) through lactation. On gd135, half the ewes from each dietary group were challenged with either 1.2 μg/kg Escherichia coli lipopolysaccharide (LPS) endotoxin, or saline as the control. The offspring's cortisol response to weaning stress was assessed 50 days postpartum by measuring serum cortisol concentrations 0, 6 and 24 h post weaning. Twenty-four hours post-weaning, lambs were subjected to an adrenocorticotropic hormone (ACTH) challenge (0.5 μg/kg) and serum cortisol concentrations were measured 0, 0.25, 0.5, 1 and 2 h post injection. At 5.5 months of age, offspring were also challenged with 400 ng/kg of LPS, and serum cortisol concentrations were measured 0, 2, 4 and 6 h post challenge. Interestingly, female offspring born to FM+LPS mothers had a greater cortisol response to weaning and endotoxin challenge compared with the other treatments, while female offspring born to SM+LPS mothers had a faster cortisol response to the ACTH stressor. Additionally, males born to FM+LPS mothers had a greater cortisol response to the ACTH challenge than the other treatments. Overall, FM supplementation during gestation combined with LPS challenge alters HPAA responsiveness of the offspring into adulthood.